Penguatan Kapasitas Pengrajin Purun: Teknologi Pengeringan, Inovasi Desain Decoupage, Dan Pemasaran Digital Di Kecamatan Pedamaran - Dwi Wulan Sari; Azqia Wardani; Maulidia Tri Yuliani; Yulian Junaidi; Khairul Fahmi Purba; Meitry Firdha Tafarini (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2026)
Purpose – Purun is utilized as a raw material for handicrafts in Ogan Komering Ilir Regency. The challenges in production and marketing remain obstacles of handicraft small enterprises. The drying process still depends on climate. Futhermore, product designs tend to be mundane, lack of colour, pattern and innovation. Then, artisans generally sell only to middlemen, resulting in low bargaining power. This community programme to enhance the artisans’ capacity. Design/methodology/approach –The programme was implemented with Rude Gebol Djuai through five activities: socialisation; preparation for training activities;  technology implementation in the form of a steel drying rack, accompanied by decoupage practice; mentoring in product development and digital marketing; and evaluation conducted through observation, discussion, and post-test. The artisans as co-implementers by contributing local knowledge, producing innovative products, and applying digital marketing. Findings – The results indicate significant improvements in artisans’ knowledge, skills, and attitudes after participating in the training (Wilcoxon test, p<0.05). Product outputs became more varied, while the drying facility supported a more orderly drying process and improved production continuity. Then, total revenue increased from IDR18,450,000 to IDR42,550,000. In addition, the adoption of e-commerce began to use. Originality/value – This programme can improving artisans’ income, empowering women, and promoting the Sustainable Development Goals (SDGs).